Unidirectional and Transverse Tensile Properties of Nanoclay Filled Kenaf/Glass Fibre Hybrid Composites - Manap, Norhashidah; Jumahat, Aidah; Arif bin Ismail, Muhammad (International Journal of Engineering and Technology, 2018)
Nowadays, hybrid continuous natural and synthetics fibre reinforced polymer nanocomposites have attracted substantial attention among researchers due to various benefits possesses by the natural fibres, synthetics fibres and nanofillers. Kenaf fibre is a natural fibre that has become one of the high potential candidates to replace synthetic fibres in polymer composite. Kenaf fibre exhibits good strength and modulus properties, low density, and non-abrasive during processing and biodegradable. Glass fibre composite has comparable modulus and strength to weight ratio properties to natural fibre composite. This study is aimed to evaluate the effect of nanoclay on longitudinal and transverse tensile properties of unidirectional (UD) kenaf/glass fibre hybrid composite (KGC). The UD KGC samples were prepared based on three different nanoclay content; i.e. 1, 3 and 5 wt. %. The 0o and 90o tensile tests were conducted in accordance to ASTM standard D3039 in order to obtain longitudinal and transverse tensile properties of unmodified and nanoclay-modified kenaf/glass composites. The results showed that the addition of nanoclay produced a substantial increase in UD tensile modulus, strength and failure strain of the KGC. UD tensile modulus, strength and strain of the KGC improved significantly by 120%, 76.4% and 68.73%, respectively, with the addition of 3wt% nanoclay when compared to the unmodified system. However, it was found that the transverse tensile properties of the KGC showed a slight increase in transverse tensile modulus, strength and strain by 16.12%, 21.85% and 30.77%, respectively, with addition of 3wt% nanoclay.Â Â Â